Injured fluoro-jade positive hippocampal neurons contain high levels of zinc after traumatic brain injury - Hellmich, Helen L. (2006)
Hippocampal damage contributes to cognitive dysfunction after traumatic brain injury (TBI). We previously showed that Fluoro-Jade, a fluorescent stain that labels injured, degenerating brain neurons, allows us to estimate the extent of hippocampal injury after experimental fluid-percussion TBI in rats. Coincidentally, we observed that injured neurons in the rat hippocampus also stained with Newport Green, a fluorescent dye specific for free ionic zinc. Here, we show that, regardless of injury severity or drug treatment, the post-TBI population of injured neurons in rat hippocampal subfields CA1, CA3 and dentate gyrus is indistinguishable, both in numbers and anatomical distribution, from the population of neurons containing high levels of zinc. Treatment with lamotrigine, which inhibits presynaptic release of glutamate and, by inference, zinc that is co-localized with glutamate, reduced numbers of Fluoro-Jade-positive and Newport Green-positive neurons equally as did treatment with nicardipine, which blocks voltage-gated calcium channels through which zinc enters neurons. To confirm using molecular techniques that Fluoro-Jade and Newport Green-positive neurons are equivalent populations, we isolated total RNA from 25 Fluoro-Jade-positive and 25 Newport Green-positive pyramidal neurons obtained by laser capture microdissection (LCM) from the CA3 subfield, linearly amplified the mRNA and used quantitative ribonuclease protection analysis to demonstrate similar expression of mRNA for selected TBI-induced genes. Our data suggest a strong association between reduced neurotoxic zinc levels after TBI and reduced hippocampal neuronal injury.